2015
DOI: 10.4141/cjas-2014-165
|View full text |Cite
|
Sign up to set email alerts
|

Licuri oil supplements for lactating cows on pasture

Abstract: (1 of licuri oil in concentrated dry matter. The intakes of dry matter, crude protein and non-fiber carbohydrate levels were not affected by the addition of licuri oil; however, the intake of neutral detergent fiber and total digestible nutrients decreased linearly. Neutral detergent fiber digestibility was reduced linearly with increasing levels of licuri oil in the concentrate. There were no changes in blood glucose levels, but blood urea nitrogen levels varied according to the time of the day when the blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The results obtained for LEA and BFT can be attributed to the fact that the goats were slaughtered at similar body weights, which corroborates the following inference drawn by Osório (2002): in carcasses of similar weights and fatness degrees, practically all body regions will have similar proportions, irrespective of the breed. In this study, this assertion was confirmed by the yield of primal cuts and the carcass morphometric measurements (Tables 3 and 4).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results obtained for LEA and BFT can be attributed to the fact that the goats were slaughtered at similar body weights, which corroborates the following inference drawn by Osório (2002): in carcasses of similar weights and fatness degrees, practically all body regions will have similar proportions, irrespective of the breed. In this study, this assertion was confirmed by the yield of primal cuts and the carcass morphometric measurements (Tables 3 and 4).…”
Section: Discussionsupporting
confidence: 84%
“…D. Y. C. de Assis et al: Carcass and meat traits of goats fed diets Therefore, producers seek alternative feed sources that allow a reduction in production costs and minimize nutritional deficiency for the development of meat goat farming. In this context, the use of biodiesel by-products in the diet of these animals may be a viable alternative, given their positive effects on meat and milk quality, as observed in other animal species (Gonzaga Neto et al, 2015;Oliveira et al, 2015). Cotton by-products have nutritional characteristics that render them good sources of nutrients for animal feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Licuri ( Syagrus coronata ) cake, a biodiesel byproduct of licuri oil generated from mechanical pressing during licuri fruit processing, contains approximately 24% crude protein (CP), 10% ether extract (EE), 52% neutral detergent fiber (NDF) and 35% g/kg acid detergent fiber (ADF) on a dry matter (DM) basis [ 7 , 10 , 11 ]. It can be used as an ingredient in the feed given to confined lambs and can increase the CP content of the meat without affecting carcass and non-carcass components [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Palm kernel cake is a product of the extraction of oil from Elaeis guineensis, which is a perennial palm tree. The diversity of favourable soils and a suitable climate for the cultivation of oil palm increases the availability of its residues throughout the year mainly in arid regions (Gonzaga et al, 2015;Lima et al, 2015;Oliveira et al, 2015aOliveira et al, , 2015b. These residues can potentially be used in animal feed because of the chemical composition of the cakes (Ferreira et al, 2012;Silva et al, 2013;Abubakr et al, 2015;Pimentel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%